Mineral composition and structural features of jewelry ammonites from mine OJSC «Mikhailovcement», Ryazan region - D. A. Petrochenkov; A. V. Petrov (Известия высших учебных заведений: Геология и разведка)
For the first time, the mineral composition and structural features of jewelry ammonite from mine OJSC «Mikhailovcement» in Ryazan Region are studied in detail. Ammonites are associated with sediments of Callovian and Oxfordian stages. Ammonites have a complex zonal structure and mainly up to 96 wt. % pyrite composition. Aragonite, sulphates of calcium and iron, calcite, quartz, apatite, organic matter, graphite, ilmenite, feldspar, mica are established. The walls and partitions of the shells retain the original aragonite composition with lamellar and prismatic layers. Of the impurity elements, heightened contents are fixed (wt.%): As — up to 0,023 and Ni — up to 0,048, and in the range of 0,001—0,01 wt. %: Co, Zn, Mo, Sr, Ba and Pb. The content of radioactive elements U, Th are at the level of background with elevated levels of carcinogenic — As and Pb. The oxidation of pyrite and the formation of a number of micro-inclusions occurred presumably with the participation of bacteria. The main part of the shell is formed by densely fused pyrite crystals of 0,2—0,5 mm in size. There are fine-crystalline and globular pyrite, located on contact with aragonite layers of the walls and partitions of shells. In this zone, most mineral micro inclusions are located. According to their decorative and technological characteristics, ammonites are high-quality jewelry material of the biomineral group. The collection of ammonite shells can be carried out along the way with the development of a mine for the extraction of cement.